Factors Affecting External Audit Quality in Municipalities of Palestine: Moderating Role of Supreme Audit Institutions - Husni Ibrahim As’ad Rabaiah
The study aims to analyze the factors of external audit quality that accountants and internal auditors believe are significant in Palestinian municipalities. Moreover, the study aims to examine the influences of the Supreme Audit Institutions (SAIs) on the links between external audit quality and its factors. These factors include auditor characteristics, audit firm attributes, and the effectiveness of municipal internal control in the municipalities. The study's data were gathered from secondary and primary sources. The secondary data was gathered from previous research as well as the annual and interim reports of the Palestinian SAIs. Furthermore, the study used a questionnaire survey that distributed to over than 309 accountants and internal auditors in 155 Palestinian municipalities who have firsthand knowledge of the financial statements under audit and are in constant contact with external auditors. SmartPLS3 software used in the statistical analysis of the data obtained from 186 survey respondents. The study found significant and positive relationships between audit quality and its determinants: auditor characteristics with dimensions of ethics, independence, and competence; audit firm attributes with dimensions of audit fees and audit firm size; and effectiveness of municipal internal control with dimensions of internal auditing, accounting basis, and laws and regulations. Furthermore, the findings revealed that supreme audit institutions moderated negatively the relationship between audit firm attributes and audit quality, but positively the relationship between auditor characteristics and audit quality, as well as the relationship between the effectiveness of municipal internal control and audit quality. This study not only contributes in expanding the literature concerning audit quality in Palestinian municipalities, it also provides meaningful guideline to the audit profession regulators and government in setting the audit standards and procedures, municipal management in hiring high-quality auditors, and audit firms in providing a high-audit quality. Finally, this study considered a few restrictions and recommendations for further investigation in new aspects of audit quality in the public sector organizations.